Under the Tightening Environment of Globalization in US and EU, Chinese Multinational Enterprise ’S International Human Reality Management’s Difference and Countermeasure——Take Oil Companies as Example - Chen, Yanwu (Transactions on Economics, Business and Management Research, 2024)
Background: United States and European countries are tightening their open policies to China, under the background of increasing tariffs and trade barriers, there is an urgent need for China's overseas trading companies to implement the necessary countermeasures to deal with the pressure on their enterprises. Oil, as a major energy source and commodity, it is more susceptible to political factors such as geopolitics and battle of national power. Method: The author searched three main keywords including international human resource management, trade war, and oil companies on CNKI and Google Scholar, through literature analysis, from the perspective of oil companies, this paper puts forward a new enlightenment for international human resource management for Chinese overseas enterprises under the background of trade war. Conclusion: In the case that China's macro conditions are difficult to change, In order to cope with the impact on seven aspects that companies may encounter, enterprises should make adjustments in seven aspects, including strategy, employees, recruitment, selection, compensation, system construction.